Competição aparente mediada pelo predador Amblyseius largoensis MUMA (Acari: Phytoseiidae) : efeito da introdução do ácaro exótico Raoiella indica HIRST (Acari: Tenuipalpidae) no ácaro nativo Oligonychus pratensis (BANKS) (Acari: Tetranychidae) - CALVET, Érica Costa (2022)
The introduction of exotic organisms can occur naturally, through the processes of dispersion or through the transit of material promoted by the anthropic trade. The effects of invading organisms in the new environment are difficult to measure, so for a long time it was quantified economic losses in agricultural crops. However, the introduction of an exotic species has environmental effects that can alter established ecological relationships, starting to compete with native fauna and/or flora, modifying ecosystems, causing displacement or extinction of species. In the western hemisphere, almost 20 years ago, an exotic mite Raoiella indica was introduced, this mite is considered an important agricultural pest of coconut and banana, two crops extensively cultivated in the countries of the Americas. The coconut tree has a rich mite fauna, and studies show a drastic reduction in species richness after the introduction of R. indica. In order to study the effect that R. indica may have on the ecological interactions existing in the coconut tree, a native herbivorous mite Oligonychus pratensis and a predator Amblyseius largoensis were selected to carry out several interaction experiments between species. The results show that R. indica and O. pratensis are negatively and asymmetrically affected competition for resource (leaflet). However, there are indications that R. indica benefits from the presence of O. pratensis when there is no resource limitation. Raoiella indica prefers to remain at the site with co-ocorrence by O. pratensis and has a better intrinsic growth rate when interacting with O. pratensis. Amblyseius largoensis prefers to feed on native prey in the most diverse situations to which it has been exposed. Raoiella indica is able to recognize A. largoensis clues in addition to showing antipredation behavior in the presence of A. largoensis clues. Therefore, the risk of displacement of O. pratensis is supported by the data generated in this work.